Diagnosing an atypical site of giant cell arteritis with magnetic resonance angiography: a case report. (December 2016) - Tan, Boon; Liu, Jonathan; Yong, Tuck; Tan, Chrismin; Li, Jordan
Abstract Background Giant cell arteritis typically involves the temporal arteries, but can involve other cranial arteries. Temporal artery biopsy is the mainstay for the diagnosis of giant cell arteritis; however, biopsy may be problematic if giant cell arteritis involves other cranial arteries that are inaccessible for sampling. In these situations, magnetic resonance angiography is a useful, non-invasive adjunctive method in the diagnosis of giant cell arteritis. In this case report, we describe a case of giant cell arteritis involving only the occipital artery which was revealed by magnetic resonance angiography. Case presentation A 67-year-old Caucasian man was admitted to our hospital with a 4-week history of malaise, fever, and mild occipital headaches. There were no other positive findings on physical examination. Laboratory studies were remarkable for normocytic anemia, raised inflammatory markers, and mildly deranged liver function tests. To exclude intracranial pathology, he underwent a cranial magnetic resonance imaging with gadolinium, which demonstrated a thickened wall and mural enhancement of his right occipital artery, consistent with giant cell arteritis. His temporal arteries were normal. His occipital arteries were not accessible for biopsy and he was commenced on high-dose prednisolone (60 mg daily). His symptoms resolved completely after a week of glucocorticoid steroid treatment and he was well on 5 mg of prednisolone once a day on follow-up. Conclusion While magnetic resonance angiography may not replace the need for biopsy, it may have a diagnostic role in suspected giant cell arteritis, such as when the involved arteries are inaccessible for biopsy.